Efficacy of dehydroepiandrosterone to overcome the effect of ovarian ageing (DITTO): a proof of principle randomised controlled trial protocol. Issue 10 (8th October 2014) - Jayaprakasan, Kannamannadiar; Narkwichean, Amarin; Maalouf, Walid E; Campbell, Bruce K
Abstract : Introduction: Dehydroepiandrosterone (DHEA) has been proposed to improve pregnancy rates in women with diminished ovarian reserve undergoing in vitro fertilisation (IVF) treatment. However, evidence regarding its efficacy is supported by a limited number of randomised controlled trials (RCTs). This double-blinded RCT aims to measure the effect of DHEA supplementation prior to and during controlled ovarian hyperstimulation on ovarian response prior to IVF treatment in women predicted to have poor ovarian reserve. Methods and analysis: Sixty women with ovarian antral follicle count ≤10 and serum anti-Mullerian hormone ≤5 pmol/L undergoing IVF/intracytoplasmic sperm injection (ICSI) treatment at the Nurture fertility clinic, Nottingham will be recruited. They will be randomised to either receive DHEA capsule 75 mg/day or placebo for at least 12 weeks before egg collection. All participants will undergo standard long down regulation protocol using human menopausal gonadotropin 300 IU/day. Serum samples and follicular fluids at the time of egg collection will be collected for hormonal immunoassays. For ICSI participants, cumulus cells stripped from oocyte will be collected for cumulus gene expression analyses regarding oocyte competence. Microdrops of oocyte culture media before the time of ICSI will be assessed for glucose, pyruvate and lactate utilisation. Embryo transfer will be performed on day 2, 3 or 5 based on the number and quality of the embryos available. Pregnancy will be defined as urine pregnancy test positive (biochemical pregnancy) and 6–8 weeks ultrasound scan with fetal heart beat (clinical pregnancy) and live birth. It is planned to perform the molecular and nutritional fingerprint analyses in batches after finishing the clinical phase of the study. Ethics and dissemination: The approval of the study was granted by the NHS Research Ethics Committee (Ref number NRES 12/EM/0002), the Medicines and Healthcare products Regulatory Agency (MHRA), and the Nottingham University Hospitals Trust Research and Development department. All participants shall provide written informed consent before being randomised into allocated treatment groups. Trial registration number: Protocol V.2.0; EudraCT number: 2011-002425-21; http://www.clinicaltrials.gov ; NCT01572025 ; CTA reference: 03057/0053/001-0002